A comprehensive review on synthesis and applications of single crystal perovskite halides. (December 2020) - Arya, Sandeep; Mahajan, Prerna; Gupta, Ramashanker; Srivastava, Ritu; Tailor, Naveen kumar; Satapathi, Soumitra; Sumathi, R. Radhakrishnan; Datt, Ram; Gupta, Vinay
Abstract: Halide based perovskite materials have fascinated strong attention for being a hopeful candidate for optoelectronic device applications. Single-crystalline halide perovskites exhibit no grain boundaries and possess low trap densities; and are therefore likely to show superior optoelectronic performances in comparison to their polycrystalline film counterparts. In spite of this, their basic perceptive of physico-chemical properties are however controversial to the scientific society. In this review article, we present the deep insight into all the reported protocols available for the synthesis of purely inorganic as well as hybrid halide perovskites (incorporating organic as well as inorganic cation) to achieve high-quality single crystals. On account of advanced characteristics like long carrier recombination lifetime and exciton diffusion length, wide-ranging visible to NIR absorption, high charge mobility, controllable optoelectronic properties etc., hybrid halide perovskites have emerged to be a tough challenger in the optoelectronic research area in comparison to the purely inorganic halide perovskites and have consequently been paid much attention. Therefore, the optoelectronic properties and convenient applications of particularly hybrid halide single-crystal perovskites in various optoelectronic devices like solar cell, laser, high energy ray detector, photodetector, light-emitting diode, etc are highlighted.